Eksploitasi Ruang Ketakutan: Analisis Peran Elit Politik dan Kelompok Penekan Dalam Upaya Sekuritisasi Islamofobia Melalui Kebijakan Imigrasi Perancis - Duanda Gumilar; Mohamad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
France is the fourth largest immigrant recipient in Europe and most of them areMuslim. Thus, France is currently ranked as the largest number of Muslim in Europe. Thiscauses domestic social and political conflict in the form of violence and discrimination knownas Islamophobia. This study aims to analyze on how the emerge of Islamophobia became adomestic threat through France immigration policy. Through the concept of linguisticconstructivism and securitization theory, this study try to analyze the development ofIslamophobia in France. This study argues that France pressure group and political eliteplay an active role in the process of politicizing Islamophobia as a security issue, so thatIslamophobia institutionalized by the France government into France immigration policysuch as prohibition of religious symbols and immigrant restriction. However, it is found abottom-up securitization process influenced by the public opinion.